2020
DOI: 10.18662/rrem/12.2sup1/292
|View full text |Cite
|
Sign up to set email alerts
|

How can Distance Learning be Used in the Physical Education of Students?

Abstract: Russian universities switched to distance students learning for before the global pandemic threat. Physical education departments are also required to provide students with distance learning opportunities. The organization of high-quality distance learning in physical education of students is not an easy task for most Russian universities. The purpose of the research-analysis of the level of effectiveness of using distance learning methods in the physical education of students in self-isolation during the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
5
0
3
Order By: Relevance
“…Osipov et al, state that the medicine students showed a higher level of adaptation to the distance learning in PE during the COVID-19 pandemic. It is possible this is related to the extensive experience in using electronic educational resources in the daily learning practice in medical education process [31]. There was a significant (p≤0.05) difference between female groups (in favour of medicine female students) in mean grading scores in PE post-cancellation of face-to-face PE classes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Osipov et al, state that the medicine students showed a higher level of adaptation to the distance learning in PE during the COVID-19 pandemic. It is possible this is related to the extensive experience in using electronic educational resources in the daily learning practice in medical education process [31]. There was a significant (p≤0.05) difference between female groups (in favour of medicine female students) in mean grading scores in PE post-cancellation of face-to-face PE classes.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps these results are related to less effective teacher-student communication in self-isolation during the COVID-19 pandemic, impossibility of performing most practical applications in PE, lack of socialization and other reasons. The most Russian university students are dissatisfied with the content of distance learning courses in PE (a significant volume of theoretical tasks), lack of motor training and lack of contact with PE teachers [31]. Significant number of Russian university students have a fairly meaningful position, considering that online PE learning is unproductive in nature, without the main physical activities and PE practical classes [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distance education has been discussed in the research in terms of challenges and effectiveness. As the difficulties in distance education, it is emphasized that it creates limitations, problems in classroom management, limitations on human resources in distance education, and limitations in applied fields (Sari & Nayir, 2020;Osipov et al, 2020;Hash, 2021). On the other hand, the research on the effectiveness of distance education has discussed the key importance of technology in school attendance, its effectiveness in developing digital skills and the advantages and disadvantages of distance education (Dinh & Nguyen, 2020;Khlaif et al, 2020;Machynska & Dzikovska, 2020).…”
Section: Conclusion Suggestions and Discussionmentioning
confidence: 99%
“…та відповідно вітчизняних, таких як: В. Кухаренко, В. Олійник, В. Рибалко, О. Свєженцев, О. Андрєєв, Г. Козлакова, І. Козубовська, Є. Полат, А. Хуторський, І. Власенко, Г. Даценко та ін. Проблеми теорії та практики дистанційного навчання у галузі фізичної культури та спорту стали предметом дослідження у працях В. Шандригось, В. Ашаніна, Л. Філенко, О. Церковної, В. Мунтяна, С. Пятисоцької, М. Булатової, А. Осіпова, П. Ладика, М. Кудрявцева та ін [2][3][4][5]9]. Але, не зважаючи на значну кількість наукових досліджень у даному напрямку, і, здавалося б, готових до дистанційної роботи закладів вищої освіти, не всі змогли оперативно та ефективно організувати процес онлайн-навчання.…”
Section: вступunclassified